2016
DOI: 10.1242/jeb.139709
|View full text |Cite
|
Sign up to set email alerts
|

Differential sex-specific walking kinematics in leghorn chickens (Gallus gallus domesticus) selectively bred for different body size

Abstract: The differing limb dynamics and postures of small and large terrestrial animals may be mechanisms for minimising metabolic costs under scale-dependent muscle force, work and power demands; however, empirical evidence for this is lacking. Leghorn chickens (Gallus gallus domesticus) are highly dimorphic: males have greater body mass and relative muscle mass than females, which are permanently gravid and have greater relative intestinal mass. Furthermore, leghorns are selected for standard (large) and bantam (sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Many birds and other animals use transitional gaits, suggesting this issue is likely widespread in extinct forms as well. Other unknowns, not quantified in the current study, but likely to further cloud the inferences from tracks in isolation are the influence of sex differences on the kinematics of locomotion [16,[68][69][70] and ontogenetic influences [21] all of which cannot be quantified in extinct animals. Inferences into the biology of extinct forms commonly suffers from large errors [60,61,71] and rely on numerous assumptions when extrapolating from extant to extinct forms [65,72,73].…”
Section: Implication For Trackways Of Extinct Animalsmentioning
confidence: 81%
“…Many birds and other animals use transitional gaits, suggesting this issue is likely widespread in extinct forms as well. Other unknowns, not quantified in the current study, but likely to further cloud the inferences from tracks in isolation are the influence of sex differences on the kinematics of locomotion [16,[68][69][70] and ontogenetic influences [21] all of which cannot be quantified in extinct animals. Inferences into the biology of extinct forms commonly suffers from large errors [60,61,71] and rely on numerous assumptions when extrapolating from extant to extinct forms [65,72,73].…”
Section: Implication For Trackways Of Extinct Animalsmentioning
confidence: 81%
“…Total length and trunk inclination explains this variation; consequently, total length is important to walking and flying [ 44 ]. According to their mass and related to their total length, partridge age-sex classes scale their CoM position with regards to walking and flying [ 45 ]. CoM position and body proportions affect mobility; less mass and better balance facilitates escape terrestrially and aerially [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the body weights of females are higher than the males. This is because the female have to incubate eggs while the male spends time looking for food and feeding until the baby birds fledge (Rose et al, 2016). Another factor that influence the weight difference is testosterone hormone.…”
Section: Morphometrics Of the Parakeetsmentioning
confidence: 99%